Persepsi Masyarakat Terhadap Program Vaksinasi Covid-19 di Desa Cepaka Kediri Tabanan - Ni Nyoman Nuartini; LP Kartiningsih SW (Jurnal Kesehatan Medika Udayana, 2022)
ABSTRACT Background and purpose: The phenomenon that is happening in the community is the implementation of the Covid-19 vaccination program, this raises the pros and cons, including the people of Cepaka Village, Kediri Tabanan. Therefore, researchers are interested in digging deeper into the public's perception of the Covid-19 vaccination Methods: The design of this study is a qualitative research with an exploratory approach. Data were collected through in-depth online interview techniques with related informants and the data were analyzed thematically which would be presented in narrative form. Results and Discussion: This study found that all informants had the perception that this Covid-19 infection was very dangerous and could cause death. The signs and symptoms that appear are not too significant, ranging from fever, cough, shortness of breath, decreased smell and stamina, but there are also sufferers who are asymptomatic. All informants made prevention efforts with 3M plus regular exercise, consuming nutritious food, vitamins and consuming homemade herbal ingredients at home. All of these informants agreed to carry out a vaccination program because they believed that the benefits of the vaccine would outweigh the disadvantages. Conclusions and Suggestions: All informants in this study understand well the dangers of Covid-19 infection and always try to do prevention with health protocols. These informants strongly agreed to be vaccinated even though they did not really understand the procedure and the impact of the vaccine. To the village and Puskesmas to further socialize this vaccination program to the community level directly. Keywords: Public perception, Vaccination, Covid-19